Design, Fabrication, and Testing of Supercapacitor Based on Nanocarbon Composite Material - Heri rustamaji Rustamaji; Tirto Prakoso; Hary Devianto; Pramujo Widiatmoko; Isdiriayani Nurdin (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
This research investigates the design, fabrication, and testing of single-cell and module supercapacitors. The supercapacitor consists of carbon nanocomposites, which contain activated carbon (AC), multiwall carbon nanotubes (MWCNT), and graphene (GR). The coin and pouch cell type supercapacitors were manufactured with AC: MWCNT: GR composite electrodes in a ratio of 70:20:10 weight percent. Meanwhile, the electrochemical characterization showed that the highest capacitance values for single coin and pouch cells were 32.13 F g-1 and 5.3 F g-1, respectively, in 6 M KOH electrolyte at a scan rate of 2 mV s-1. Furthermore, the power and energy densities for the coin-cell supercapacitor were 69 W kg-1 and 6.6 Wh kg-1, respectively, while for the pouch cell, it was 7.4 W kg-1 and 1.0 Wh kg-1, respectively. The coin-cell supercapacitor durability test was carried out for 1000 cycles, yielding the retention capacitance and coulombic efficiency values of 94-97% and 100%, respectively. These results showed that the performance of the supercapacitor is close to commercial products.